먼쪽 노뼈 골절환자에게 적용한 칼텐본-에반스 관절가동술의 적용 횟수가 노자관절의 운동성, 통증, 기능과 악력에 미치는 영향 - 김명진; Myoung-jin Kim; 서동권; Dong-kwon Seo; 이연섭; Yeon-seop Lee (Journal of the Korean Society of Integrative Medicine, 2022)
Purpose : The purpose of this study was to investigate the effects of Kaltenborn-Evjenth (KE) joint mobilization of the distal radioulnar joints (RUJ) and proximal RUJ in distal radius fractures (DRFs) on range of motion (ROM), grip strength (GS), and patient-written wrist evaluation (PRWE) in each group once, thrice, or fivefold. Methods : Forty-two subjects participated in this study. We divided the subjects with DRFs into groups applying KE concepts RUJ mobilization once, thrice, and fivefold. The patients' ROM and GS were measured using a joint goniometer and dynamometer, respectively. Pain and function were also assessed using a PRWE. In the statistical analysis, all data were tested for normality using the Shapiro-Wilk test, and paired t-tests were performed for within-group before-and-after comparisons of each intervention. One-way analysis of variance was used for between-group comparisons of differences. All statistical significance levels were set at α=.05. Results : There were significant differences in the ROM in all three groups before and after the intervention (p<.05), but there were no significant differences between the groups. There were significant differences in the GS in the three groups before and after the intervention (p<.05), but there were no significant differences between the groups. In the pain part of the PRWE, all three groups had significant differences before and after intervention (p<.05), but there was no significant difference between the groups. In the functional part of the PRWE, there were significant differences in the three groups before and after intervention (p<.05), but no significant difference occurred between the groups. Conclusion : Based on the aforementioned results, there were no significant between-group differences in ROM, GS, and PRWE (pain and function) after the application of the K-E joint mobilization to DRFs once, thrice, and fivefold. Nevertheless, there were significant within-group differences in all the above.